A contribution to the Atherigona (Diptera, Muscidae) fauna of Angola - Mokome M. J. Magoai; Burgert S. Muller; Terence A. Bellingan (African Invertebrates)
This study lists a total of 13 species of Atherigona Rondani, 1856 from Angola, 9 of which were previously recorded: Atherigona (Atherigona) bedfordi van Emden, 1940; Atherigona (Atherigona) campestris Deeming, 1971; Atherigona (Acritochaeta) cogani Deeming, 1981; Atherigona (Atherigona) laevigata (Loew, 1852); Atherigona (Atherigona) lineata ssp. lineata (Adams, 1905); Atherigona (Atherigona) lineata ssp. ugandae van Emden, 1940; Atherigona (Atherigona) matilei Deeming, 1977; Atherigona (Atherigona) mirabilis ssp. mirabilis Deeming, 1971; Atherigona (Acritochaeta) orientalis Schiner, 1868; and Atherigona (Atherigona) ruficornis Stein, 1913. One previously described species, Atherigona (Atherigona) albistyla Deeming, 1971, has now been added as a new record. Three species are newly described: Atherigona (Atherigona) adelinahae Magoai, sp. nov., Atherigona (Atherigona) angolaensis Magoai, sp. nov., and Atherigona (Atherigona) cuanavaleensis Magoai, sp. nov. A key to the males of Atherigona species is provided, along with brief generic diagnoses of the new species and illustrations of most Angolan species.